Age Increase of Estrogen Receptor-α (ERα) in Cortical Astrocytes Impairs Neurotrophic Support in Male and Female Rats - Arimoto, Jason M. (Endocrine Society, 2013)
Rodent models show decreased neuronal responses to estradiol (E2) during aging (E2-desensitization) in association with reduced neuronal estrogen receptor (ER)-α, but little is known about age changes of E2-dependent astrocytic neurotrophic support. Because elevated expression of astrocyte glial fibrillary acidic protein (GFAP) is associated with impaired neurotrophic activity and because the GFAP promoter responds to ERα, we investigated the role of astrocytic ERα and ERβ in impaired astrocyte neurotrophic activity during aging. In vivo and in vitro, ERα was increased greater than 50% with age in astrocytes from the cerebral cortex of male rats (24 vs 3 months), whereas ERβ did not change. In astrocytes from 3-month-old males, experimentally increasing the ERα to ERβ ratio induced the aging phenotype of elevated GFAP and impaired E2-dependent neurite outgrowth. In 24-month-old male astrocytes, lowering ERα reversed the age elevation of GFAP and partially restored E2-dependent neurite outgrowth. Mixed glia (astrocytes to microglia, 3:1) of both sexes also showed these age changes. In a model of perimenopause, mixed glia from 9- to 15-month rats showed E2 desensitization: 9-month regular cyclers retained young-like ERα to ERβ ratios and neurotrophic activity, whereas 9-month noncyclers had elevated ERα and GFAP but low E2-dependent neurotrophic activity. In vivo, ERα levels in cortical astrocytes were also elevated. The persisting effects of ovarian acyclicity in vitro are hypothesized to arise from steroidal perturbations during ovarian senescence. These findings suggest that increased astrocyte ERα expression during aging contributes to the E2 desensitization of the neuronal responses in both sexes.